Potential of Polymeric Materials (Microcrystalline Cellulose and Cotton Fibers) for the Removal of Anionic Dye from Textile Wastewater through Solid Phase Extraction - Dar, Amara; Safdar, Amna; Anwar, Jamil (Journal of Environmental Science and Engineering Technology, 2019)
Alizarin red S dye is frequently used in textile industry and thus present in large quantities in out-drained industrial effluents, which pollute the sources of fresh water, by hindering the light and affecting the aquatic flora and fauna. Such water when used in irrigation purposes later causes threats for human health and animals life. In this work the dye has been effectively removed by using two polymeric materials i.e. microcrystalline cellulose and cotton fiber by solid phase extraction. Various concerned physical parameters were optimized for maximum adsorption through batch experiments. Kinetics of the adsorption process, thermodynamic studies, isotherm studies and desorption of the dye have also been studied. Qmax values for cotton and microcrystalline cellulose come out to be 6.612 mg/g and 5.573mg/g. Further this extraction proved to be spontaneous and endothermic in nature.